A contribuição do uso da gamificação digital no processo de ensino-aprendizagem de alunos com transtorno do neurodesenvolvimento no município de Tucuruí - SILVA, Thales Maurício Gonçalves da (2024)
Digital gamification has been explored as an innovative strategy in education, especially relevant for teaching students with neurodevelopmental disorders such as Autism Spectrum Disorder (ASD) and Attention Deficit Hyperactivity Disorder (ADHD). These students face additional challenges in the school environment, and gamification, by integrating game elements into educational activities, may contribute to their cognitive and social development. Motivated by a background in Computer Engineering and an interest in inclusive technologies, this research seeks to answer the following question: how can digital gamification contribute to the teaching-learning process of students with neurodevelopmental disorders in the public schools of Tucuruí? Focusing on the Municipal Elementary School Darcy Ribeiro and the Municipal Preschool Unit Plácido de Castro, the main objective was to analyze the effectiveness of gamification on aspects such as engagement, motivation, and learning of these students. The research followed a qualitative approach, allowing the observation of the impact of game elements, such as rewards, challenges, and immediate feedback, in the real school environment. The results indicate that gamification promotes an inclusive environment, reduces stress, and encourages socialization, personalizing the learning experience for neurodivergent students. This analysis culminates in recommendations for the ethical and effective implementation of digital gamification, contributing to a more adaptive and inclusive education in public schools.